PERAN TU’A GOLO SEBAGAI PEMIMPIN TERTINGGI DALAM STRUKTUR SOSIAL KELOMPOK ETNIK MANGGARAI DITINJAU DARI PERSPEKTIF LINGUISTIK KEBUDAYAAN - Fransikus Bustan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2009)
Abstract This study examines roles of tu’a golo as top leader in social structure Manggarai ethnic group in terms of cultural linguistics, with reference to characteristics of forms and meanings of verbal expressions used as attribute-adjectives for tu’a golo. This study is descriptive based on phenomenology. Methods and techniques of data collection are observation, interview, focus group discussion, recording, note-taking, and documentation study. Data sources are Manggarai ethnic group representing by four key informants. Data is analyzed qualitatively by using inductive method and encoding technique. Result of study shows, requirement for tu’a golo is primogenitor having spiritual authority. As top leader in social structure of wa’u as patrilineal-genealogic clan, tu’a golo shares executive and judicative role, acting as traditional house manager, clan leader, and village chief. It suggested revitalizing roles of tu’a golo to be partner of Manggarai government in succeeding community development programs.